Sleep Duration and Diabetic Kidney Disease - Tan, Nicholas Y. Q.; Chan, Joel; Cheng, Ching-Yu; Wong, Tien Yin; Sabanayagam, Charumathi (Frontiers in Endocrinology, 2019)
Aims: Abnormally short or long durations of sleep have been proposed as a risk factors for diabetes and its micro- and macro-vascular complications. However, the relationship between sleep duration and diabetic kidney disease (DKD) has not been well-characterized. Thus, we aimed to examine the association of sleep duration with DKD in two Asian populations. Methods: We included 1,258 persons (Malay, n=403; Indian, n=855) aged 40-80 years with diabetes from a population-based cross-sectional sample from Singapore. DKD was defined by low estimated glomerular filtration rate (eGFR <60 mL/min/1.73m2) and albuminuria (urinary albumin-to-creatinine ratio ≥30 mg/g, only measured in Indian participants). Self-reported habitual sleep duration was categorized into 4 categories: very short (<5 h), short (5 to 6.9 h), normal (7-8 h) and long (>8 h). The associations of sleep duration with low eGFR and albuminuria were analysed using multivariable logistic regression models adjusted for multiple potential confounders (including classic risk factors such as HbA1c and hypertension). Results: In total, 268 (21.3%) participants had low eGFR, and 271 (34.7% in Indians) had albuminuria. The number (%) of individuals with very short, short, normal, and long durations of sleep were 117 (9.3%), 629 (50.0%), 429 (34.1%), and 83 (6.6%), respectively. Long sleep duration was associated with a higher odds of renal insufficiency compared to normal sleep duration (OR [95% CI]: 2.31 [1.27 – 4.19]) on multivariable analysis. Similarly, both long and very short durations of sleep were associated with higher odds of albuminuria (OR [95%]: 2.44 [1.36, 4.38] and 2.37 [1.25, 4.50], respectively) in Indian participants (where data on albuminuria were available) Conclusions: Our study suggests that abnormally short or long durations of sleep were associated with DKD, manifesting as either a reduced eGFR or increased albuminuria. However, further longitudinal data would be required for confirmation.